Genomic rearrangements in childhood spinal muscular atrophy: linkage disequilibrium with a null allele. Issue 2 (February 1995) - Daniels, R J; Campbell, L; Rodrigues, N R; Francis, M J; Morrison, K E; McLean, M; MacKenzie, A; Ignatius, J; Dubowitz, V; Davies, K E
Abstract : Autosomal recessive childhood onset spinal muscular atrophy has been mapped to chromosome 5q13. We report the analysis of a polymorphic microsatellite which shows linkage disequilibrium with the disease. The linkage disequilibrium is observed with a null allele which is seen as the non-inheritance of alleles from one or both parents. The inheritance of a null allele was observed in 26 out of 36 (72%) informative childhood onset spinal muscular atrophy (SMA) families tested, of all types of severity and from a variety of ethnic backgrounds. In seven families segregating for the severe Werdnig-Hoffmann or SMA type I, no alleles were inherited from either parent using this microsatellite. This null allele may represent a deletion which is either closely associated with, or causes, the disease.